Interfacial failure modelling of diamond bits made of particulate composites. (1st November 2016) - Xu, J.; Sheikh, A.H.; Xu, C.
Abstract: The failure analysis of diamond impregnated bits, which are found as particulate composite materials consist of diamond particles randomly distributed within a metal matrix, is conducted to study the pull out behaviour of diamond grits for an assessment of diamond retention capacity of these drilling bits. The finite element technique is used to model the diamond-matrix system where a zero thickness surface based cohesive zone modelling technique is used to simulate the failure at the interface between the matrix and the diamond particle. For the validation of the model, few numerical examples are initially solved and the results produced by the model are compared with the published results which show a good performance of the model. Finally, a parametric study is conducted to show the effects of shapes, orientations and protrusions of diamond particles as well as interface properties on the retention capacity of diamond particles.